2018
DOI: 10.19177/memorare.v5e12018136-152
|View full text |Cite
|
Sign up to set email alerts
|

De Gana para o Brasil: o desejo de encontrar uma grama mais verde

Abstract: Neste artigo, analisaremos os reflexos do entremeio migratório materializado na fala de um dos imigrantes ganeses que mora na cidade de Tubarão – SC. O contato com o imigrante se deu a partir do Projeto de Extensão Acolhida ao Migrante, desenvolvido na Universidade do Sul de Santa Catarina (Unisul), que tem como proposta não só oportunizar a aprendizagem da Língua Portuguesa, mas também a inserção no espaço social. Buscamos, ao trazer o tema migração, tecer uma análise discursiva a partir dos aspectos linguíst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…A second action identified by Bellandi et al (2021), Jungblut et al (2018) and Silva et al (2020b), found that partnerships between governments, universities, civil society and companies are fundamental support to refugees who, when dealing with social and legal issues, face the challenges of overcoming the local bureaucracy to obtain personal documents. Bayuo et al (2020), Bacher (2019), Anjos (2018), Chopra (2020), Silva et al (2020b) and Marcu (2018) corroborate the findings of the previous authors stating that in addition to fostering refugees with social and legal information, universities should be protagonists in basic and specialized health care, such as psychological, dental and others.…”
Section: Resultssupporting
confidence: 85%
“…A second action identified by Bellandi et al (2021), Jungblut et al (2018) and Silva et al (2020b), found that partnerships between governments, universities, civil society and companies are fundamental support to refugees who, when dealing with social and legal issues, face the challenges of overcoming the local bureaucracy to obtain personal documents. Bayuo et al (2020), Bacher (2019), Anjos (2018), Chopra (2020), Silva et al (2020b) and Marcu (2018) corroborate the findings of the previous authors stating that in addition to fostering refugees with social and legal information, universities should be protagonists in basic and specialized health care, such as psychological, dental and others.…”
Section: Resultssupporting
confidence: 85%